Upregulation of sialidase NEU3 in head and neck squamous cell carcinoma associated with lymph node metastasis. Issue 11 (16th October 2015) - Shiga, Kiyoto; Takahashi, Kohta; Sato, Ikuro; Kato, Kengo; Saijo, Shigeru; Moriya, Setsuko; Hosono, Masahiro; Miyagi, Taeko
Abstract : Regional lymph node metastasis in head and neck squamous cell carcinoma (HNSCC) is a crucial event for its progression, associated with a high rate of mortality. Sialidase, a key enzyme for the regulation of cellular sialic acids through catalyzing the initial step of degradation of glycoproteins and glycolipids, has been implicated in cancer progression. To facilitate the development of novel treatments for HNSCC, we have investigated whether sialidase is involved in the progression of this cancer. We found plasma membrane‐associated sialidase (NEU3) to be significantly upregulated in tumor compared to non‐tumor tissues; particularly, an increase in its mRNA levels was significantly associated with lymph node metastasis. To understand the mechanisms, we analyzed the NEU3‐mediated effects on the malignant phenotype using squamous carcinoma HSC‐2 and SAS cells. NEU3 promoted cell motility and invasion, accompanied by the increased expression of MMP‐9, whereas NEU3 silencing or the activity‐null mutant did not. NEU3 enhanced phosphorylation of epidermal growth factor receptor (EGFR), and an EGFR inhibitor, AG1478, abrogated the NEU3‐induced MMP9 augmentation. These findings identify NEU3 as a participant in HNSCC progression through the regulation of EGFR signaling and thus as a potential target for inhibiting EGFR‐mediated tumor progression. Abstract : Regional lymph node metastasis in head and neck squamous cell carcinoma (HNSCC) is a crucial event for its progression, with a high rate of mortality. To improve the treatment, we studied sialidase expression in HNSCC and discovered the sialidase NEU3 to be significantly up‐regulated in the specimens of the patients associated with lymph node metastasis. NEU3 was further found to play a novel role in regulating MMP9 expression through activation of EGFR signaling, leading to enhanced cell invasion and migration.